Interventional Radiology and the Care of the Oncology Patient - Siobhan B. O'Neill; Owen J. O'Connor; Max F. Ryan; Michael M. Maher (Radiology Research and Practice)
Interventional Radiology (IR) is occupying an increasingly prominent role in the care of patients with cancer, with involvement from initial diagnosis, right through to minimally invasive treatment of the malignancy and its complications. Adequate diagnostic samples can be obtained under image guidance by percutaneous biopsy and needle aspiration in an accurate and minimally invasive manner. IR techniques may be used to place central venous access devices with well-established safety and efficacy. Therapeutic applications of IR in the oncology patient include local tumour treatments such as transarterial chemo-embolisation and radiofrequency ablation, as well as management of complications of malignancy such as pain, organ obstruction, and venous thrombosis.